ECOFRIENDLY MANAGEMENT OF FUSARIUM FRUIT ROT OF CITRUS - T. T. BARIA; R. K. PATIL; J. K. PATEL (The Bioscan, 2015)
Fruit rot disease caused by Fusarium pallidoroseum is one of the major post-harvest disease of citrus and is adversely affects the fruit quality and the market value. In present study various antagonists and culture filtrate of antagonists were screened to know their bio efficacy in controlling the Fusarium fruit rot of citrus. Trichoderma viride, T. harzianum, T. virens, T. atroviridae, T. asperellum, and T. fasciculatumin significantly inhibit 100 % mycelial growth of F. pallidoroseum in vitro study, while in case of in vivo study lowest Fusarium rot severity was observed in fruits treated with Trichoderma viride both in pre- (15.30 %) and post-inoculation (17.08 %) methods at 8 th day after inoculation. All the culture filtrate of antagonists found effective in inhibiting the mycelial growth of over control in in vitro. Lowest mycelial growth (29.63 mm) and significantly highest per cent mycelial growth inhibition was recorded in culture filtrate of T. viride (65.28 %). It was also found significantly most effective in reducing the Fusarium rot severity both in pre- (9.23 %) and post-inoculation (13.16 %) methods after 8 th day of inoculation.